Concurrent training in cardiac rehabilitation: A scoping review of aerobic-strength combinations in patients with coronary artery disease - Aliff Latir; Eliza Hafiz; Anwar Suhaimi (PLoS ONE, 2026)
Concurrent training (CT), defined as the integration of aerobic and strength exercise modalities, is increasingly implemented within cardiac rehabilitation (CR) to improve cardiovascular and musculoskeletal health. However, CT prescriptions vary markedly, and the characteristics and application of CT within CR have not been comprehensively mapped. This scoping review examined how CT has been designed and delivered in CR and summarised reported outcomes across International Classification of Functioning, Disability and Health (ICF) domains. A systematic search of databases and supplementary sources was conducted from October 2023 to December 2025. Clinical trials evaluating CT compared with usual care or aerobic training alone were eligible. Fourteen trials (n = 1,037; 13 randomised, 1 single-group) were included. CT programmes varied widely in setting (hospital, community, hybrid), CR phase (II–III), duration (5–32 weeks), and training structure. Aerobic training was delivered using continuous aerobic training (CAT), aerobic interval training (AIT), or high-intensity interval training (HIIT), with intensities prescribed using peak oxygen uptake (V̇O₂peak), maximum heart rate (HR max ), heart rate reserve (HRR), work rate, ventilatory threshold, or rating of perceived exertion (RPE). Modalities ranged from cycle ergometers and treadmills to multimodal or circuit-based formats. Strength-training prescriptions differed in targeted muscle groups, sets (2–8), repetitions (8–20), equipment (e.g., machines, free weights, TheraBand), and intensity anchors (% of one repetition maximum, RPE, % of maximum voluntary contraction). Application of progressive overload was inconsistent across studies. Exercise capacity (primarily V̇O₂peak) and muscle strength were the most consistently assessed outcomes. No CT-related adverse events were reported. CT has been applied using diverse delivery formats and exercise prescriptions within CR. Physiological outcomes were most consistently measured, whereas activity and participation-level outcomes showed greater variability and limited long-term evaluation. Future research should prioritise clearer reporting of training parameters, examine CT within community and hybrid CR models, incorporate behavioural and patient-reported outcomes, and investigate sex-specific responses and long-term effects to inform scalable and contextually adaptable CT approaches.